Todd Kontje. Imperial Fictions: German Literature Before and Beyond the Nation-State. U of Michigan P, 2018. - Patricia A. Simpson (Studies in 20th & 21st Century Literature, 2021)
Review of Todd Kontje. Imperial Fictions: German Literature Before and Beyond the Nation-State. U of Michigan P, 2018. 329 pp.
Keywords: Germany literary history; empire; nation